A versatile toolkit for overcoming AAV immunity - Li, Xuefeng; Wei, Xiaoli; Lin, Jinduan; Ou, Li (Frontiers in Immunology, 2022)
Recombinant adeno-associated virus (AAV) is a promising delivery vehicle for in vivo gene therapy and has been widely used in >200 clinical trials globally. There are already several approved gene therapy products, e.g., Luxturna and Zolgensma, highlighting the remarkable potential of AAV delivery. In the past, AAV has been seen as a relatively non-immunogenic vector associated with low risk of toxicity. However, an increasing number of recent studies indicate that immune responses against AAV and transgene products could be the bottleneck of AAV gene therapy. In clinical studies, pre-existing antibodies against AAV capsids exclude many patients from receiving the treatment as there is high prevalence of antibodies among humans. Moreover, immune response could lead to loss of efficacy over time and severe toxicity, manifested as liver enzyme elevations, kidney injury, and thrombocytopenia, resulting in deaths of non-human primates and patients. Therefore, extensive efforts have been attempted to address these issues, including capsid engineering, plasmapheresis, IgG proteases, CpG depletion, empty capsid decoy, exosome encapsulation, capsid variant switch, induction of regulatory T cells, and immunosuppressants. This review will discuss these methods in detail and highlight important milestones along the way.